Enhanced photocatalytic performance of Nb doped TiO2/reduced graphene oxide nanocomposites over rhodamine B dye under visible light illumination - Neradabilli Prabhakarrao (BMC, 2021)
Abstract The present study discusses the synthesis of Nb doped TiO2/reduced graphene oxide (rGO) intercalated nanocomposites via sol-gel route at a lower temperature by using different loading amounts of graphene oxide (GO) (1 to 10 wt%). The synthesized composite materials were further characterized by copious instruments such as X-ray Diffractometer, UV-Vis Diffuse Reflectance Spectroscopy, Scanning Electron Microscopy, Transmission Electron Microscopy, Brunauer-Emmett-Teller surface area analysis, Raman and Fourier Transform-Infrared Spectroscopy. The experimental results stated that the Nb doped TiO2 nanoparticles uniformly distributed on the surface of rGO with an interfacial linking bond between TiO2 and rGO. Later, the photocatalytic degradation of Rhodamine B (RhB) dye using produced materials under visible light irradiation was examined. These results revealed that Nb doped TiO2/rGO nanocomposites exhibited better photocatalytic performance than Nb doped TiO2 for the removal of RhB dye. However, among all, the nanocomposite having 5 wt% of GO content achieves the highest degradation efficiency for RhB dye approximately 98% under visible light exposure. Altogether, the unique properties such as electron accepting and transporting properties of GO in the nanocomposite is caused to enhance photocatalytic activity by minimizing the charge carrier’s recombination rate.